Does Public Sector Inefficiency Constrain Firm Productivity : Evidence from Italian Provinces - Giordano, Raffaela (IMF Working Papers; Working Paper ;, 2015)
This paper studies the effect of public sector efficiency on firm productivity using data from more than 400,000 firms across Italy's provinces. Exploiting the large heterogeneity in the efficiency of the public sector across Italian provinces and the intrinsic variation in the dependence of industries on the government, we find that public sector inefficiency significantly reduces the labor productivity of private sector firms. The results suggest that raising public sector efficiency could yield large economic benefits: if the efficiency in all provinces reached the frontier, output per employee for the average firm would increase by 9 percent.